The Image of Lesbians in the Short Story "When Everyone Rejected My Presence Nearby" by Yael Stefany Sinaga - Fatimah, Ade Fitria (Journal of Literary Prose and Society, 2025)
This paper aims to describe the image of lesbians in the short story "When Everyone Rejects My Presence Nearby" by Yael Stefany Sinaga which was published in 2019 on the Suarausu.co.id page. This short story was criticized by the rectorate of the University of North Sumatra (USU) for telling the life experience of a lesbian woman who fell in love with her female friend. This short story was chosen as the object of research because there is a depiction by the author of the life of being a lesbian and provides several views on lesbians. This research uses qualitative research methods. The data is analyzed through words, sentences, and dialogues that show the image of lesbians narrated in this short story. The results of this study show that the author describes a lesbian as someone who is considered despicable and disgusting by others. The author also portrays lesbians as not feeling that being a lesbian is wrong because she also loves her female partner seriously.